A Study on the production system of Solid Cement Corporation - Lerio, Lourberto (College of Engineering, 1995)
This Production Systems study of Solid Cement Corporation was taken in partial fulfillment of the course in I.E. 151. The main thrust of this study is to improve the Inventory control of spare parts of the company and to generate workable recommendations. This study involves the overall production system of the company. This includes Purchasing, Warehousing, Production Process, Working conditions, Quality COntrol, Environmental Control, Distribution and Personnel. The company is producing Portland Cement with the brand name Island Cement. The group conducted its study at PHINMA, Makati and at Tagbac, Antipolo, Rizal. The group obseerved that in purchasing the company only have one vendor in one of its vital raw material. In the production process, the equipments are in full capacity with sensors to predetermining upcoming malfunctions. In the working condition of the workers, the workers don't use the face mask properly and the absence of fire extinguisher to fire prone area can also be observed. In quality control, raw materials, in process materials and finished products are properly monitored resulting to high quality portland cement. The company is pushing through in greening the plantsite. In the warehouse section, the group noticed that its warehouse area is not fully utilized, it has a poor warehouse layout resulting to overcrowding and poor housekeeping. Obsolete materials are scattered with no proper classification. Some parts are exposed outside the warehouse to the changing weather. In the manual encoding of the inventory, the workers commit errors since their computer only has an encoding system. They don't classify their parts, with common function in some production lines, properly. These resulted to poor tracking system of the spare parts. The process department lack communications with the warehouse resulting to reordering of materials even if its inventory level is still capable of providing its needs. The company should provide ergonomically designed face mask best suited for cement plants and provide fire extinguisher at fire prone areas.It should utilize to the fullest its warehouse area. It should provide a better computer technology to handle the high volume of information it process daily with a network system with the department affected by the inventory levels of the spare parts. It should implement a good inventory control on their spare parts to avoid lost inventory like barcoding their inventory.